Karakterisasi Soyghurt dengan Penambahan Pisang Tuntung Pandang dengan Variasi Waktu Fermentasi - Linangsari, Titis; Lestari, Ema; Habidiyah, Siti; Fatimah, Fatimah (AGRITROPICA : Journal of Agricultural Sciences, 2025)
Soyghurt is one of the beverage products from soy milk, which is produced through a fermentation process by lactic acid bacteria (LAB). The bacteria commonly used are Lactobacillus bulgaricus and Streptococcus thermophilus. This study aimed to analyse the quality of the physical and chemical properties of banana yoghurt with various fermentation times. The method used in this research involves making soy yoghurt products through four stages of fermentation: 6 hours, 12 hours, 18 hours, and 24 hours. The quality analysis performed was physical analysis (viscosity test and pH test), chemical analysis (ash content test, acid content test, and protein test), and organoleptic properties (hedonic test and hedonic quality test). Then, an analysis of the ANOVA test was conducted to determine the average of more than two groups of data by comparing the variances and describing the total data. Based on the results of the study, it can be interpreted that the analysis of the quality of banana soyghurt with various physical and chemical showed results, namely the viscosity between 51.00cp - 55.05cp, pH test 5.27 - 4.18, ash content 0.37% - 0.49%, test for acid content 0.50% - 0.72%, and test for protein 2.18%, and the organoleptic test for hedonic panelists is somewhat like texture, somewhat like the taste, liked the aroma and somewhat liked the color, for hedonic quality slightly thick texture, sour flavour, distinctive pungent soyghurt aroma, and yellowish white color.